The heart of the mountains [large type] - Basham, Pepper (Thorndike Press large print Christian romance series., 2022)
"To escape a forced marriage, Cora Taylor travels from England to the Blue Ridge Mountains in search of her brother, who is working as a teacher in a mission school. She hopes to find a place where her nursing skills and independent ideas will be accepted and appreciated, but nothing prepares her for the wild mixture of isolation, community, brokenness, and hope within these mountains...or in the person of Jeb McAdams. Returning from the devastation of World War 1 emotionally damaged, Jeb McAdams struggles against the rampant mountain alcoholism to soothe his nightmares. It's easy to hide within the mountains, or it was, before Cora Taylor arrived. Now, she seems to show up at every turn, bringing her modern ideas, curiosity, and beautiful eyes with her. Bound by their shared war history, the pair develop an unlikely friendship, which unexpectedly hints to something more. But when Cora's desire to help the women of the mountains crosses an unspoken line, will Jeb be able to protect this feisty flatlander from the wrath of the mountain men or will he end up losing much more than his heart?"--